Moral Development and The Enhancement Of Students’ Religiosity From A Socio-Psychological Perspective Through The Pesantren Program - Arifin, Zaenal; Shobirin, Muhammad (LP2M IAIN kUDUS, 2025)
This study aims to analyze the efforts to cultivate moral character and enhance students’ level of religiosity through the pesantren (Islamic boarding school) program at MTs. Al-Ikhlas Margorejo Pati, using social and psychological approaches. The background of this research is based on the phenomenon of deviant behaviors among madrasah students, such as truancy, disrespect toward teachers, bullying, and negligence in performing obligatory religious practices. The pesantren program was initiated as a solution for religious character education and the strengthening of moral values. This study employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation. The research subjects consisted of the head of the madrasah, pesantren caregivers, teachers, and students. Analysis using Michel Foucault’s theory of power relations reveals that the process of moral and religious cultivation occurs through mechanisms of discipline, supervision, and the internalization of religious values. The pesantren environment functions as a social space that produces religious subjects through productive power relations among caregivers, ustadz (religious teachers), and santri (students). From a socio-psychological perspective, the pesantren serves as an arena for identity formation and emotional balance during adolescence. The study recommends that the pesantren management model be integrated with the formal education system as an effective strategy for shaping students’ religious character amid the challenges of globalization.